Anteseden Penyebab Lama Studi Mahasiswa pada Program Sarjana Ilmu Administrasi Publik - Afiliani Lamut Fonge, Gamelia; Pradana, I Putu Yoga Bumi; Daut Niga, Jacoba (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research was conducted to find out what factors influence the length of study of students of the State Administration Study Program. The theory used in this research is the theory of Slameto which states that the factors that influence the length of study of students are internal and external factors. In this study, researchers used a qualitative approach with a case study type of research. Informants totaled 16 people. The data analysis techniques used are data collection, data reduction, data presentation, conclusions and verification. The results of this study indicate that the factors that influence the length of study of students are internal factors and external factors. Internal factors include: the physical condition of students, each student tries to motivate himself, while for student learning habits it is not good because many students are lazy to read books and do assignments by copying from the internet. While external factors are: family economic factors, institutional factors, less influence because the State Administration Study Program has been very helpful for students to complete their studies on time, only because students are lazy to work on their thesis so that their study period becomes long, environmental factors, the community environment does not affect the length of study of students because it depends on the student, if students can divide their time between lectures and organizations, it will not affect their studies.